A new magnetic adsorbent of eggshell-zeolitic imidazolate framework for highly efficient removal of norfloxacin. Issue 48 (26th November 2021) - Zhong, Yuyu; Chen, Chen; Liu, Si; Lu, Chengyu; Liu, Dong; Pan, Ying; Sakiyama, Hiroshi; Muddassir, Mohd.; Liu, Jianqiang
Abstract : A new Fe3 O4 -ES/ZIF-8 was synthesized via a facile method and was used to remove the norfloxacin with a high efficiency of 80.13%. The magnetic nature of the adsorbent caused to an easy separation from aqueous solution. Abstract : Many effluents contain various antibiotics commonly, where the simultaneous removal of them is a big challenge. In this study, the magnetic biocomposite (eggshell-zeolitic imidazolate framework) was designed and synthesized by green and facile method. Zeolitic imidazolate framework-8 (ZIF-8) particles were stabilized on the surface of magnetic eggshell (Fe3 O4 -ES), generating a new Fe3 O4 -ES/ZIF-8 adsorbent, which was also fully characterized using FTIR, XRD, SEM and BET techniques. Thereafter, norfloxacin (NOR) adsorption processes were investigated through different influencing factors (dosage, concentration, pH and temperature). The Langmuir adsorption isotherm could confirm a maximum removal efficiency of 80.13% for NOR. Kinetic studies illustrated that the pseudo-first-order model was in line with the experimental data of the simultaneous removal of NOR. Moreover, the magnetic nature of the adsorbent caused an easy separation from the aqueous solution.